A natureza jurídica dos certificados de emissões reduzidas (CERs) e seus efeitos legais no Brasil - Brunetti, Anderson Ivanhoé (2011)
The objective of this research is to contribute to the study of the legal definition of Certified Emission Reductions (CERs) and its legal implications for contract negotiation and local sales tax. These definitions will provide greater transparency and legal certainty for negotiations in the carbon market defined by the Kyoto Protocol. The methodology used in the study was to analyze the current National Legislation, literature from government sources and international research organizations. The study showed that the most viable legal classification for CERs is intangible, because the certificates can be equaled to a right which the Clean Development Mechanism (CDM) certificate holder has after its approval. From the understanding of the legal nature of CERs as intangible, we performed an analysis of contractual arrangements applied during the negotiations of the licenses and taxes that could be incident on the certificates. The contract type that was the most appropriate for the negotiation of licenses was the promise to transfer or assignment of future intangibles. In relation to taxation, taxes were the main Income Tax of Legal Entities and the Tax on Financial Operations. However, a full tax exemption could attract interest from new investors in CDM projects, which would result in a more sustainable environmental and socioeconomic development.